2022
DOI: 10.1038/s42004-021-00613-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the ZIF-L to ZIF-8 transformation from fundamentals to fully costed kilogram-scale production

Abstract: The production of MOFs at large scale in a sustainable way is key if these materials are to be exploited for their promised widespread application. Much of the published literature has focused on demonstrations of preparation routes using difficult or expensive methodologies to scale. One such MOF is nano-zeolitic imidazolate framework-8 (ZIF-8) – a material of interest for a range of possible applications. Work presented here shows how the synthesis of ZIF-8 can be tracked by a range of methods including X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 65 publications
7
54
0
Order By: Relevance
“…The application of a Fourier transform clearly revealed that the Zn clusters (bright dots of lattice image at the unit cell vertices) projected a regular hexagonal structure as anticipated, forming a hexagonal honeycomb lattice (Figure d1). The results of selected-area electron diffraction patterns (SADPs) and EDS confirmed the successful preparation of ZIF-8@GO, with evidence of a (114) crystal plane and an inner element of ZIF-8 (Figure d2–d3) …”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The application of a Fourier transform clearly revealed that the Zn clusters (bright dots of lattice image at the unit cell vertices) projected a regular hexagonal structure as anticipated, forming a hexagonal honeycomb lattice (Figure d1). The results of selected-area electron diffraction patterns (SADPs) and EDS confirmed the successful preparation of ZIF-8@GO, with evidence of a (114) crystal plane and an inner element of ZIF-8 (Figure d2–d3) …”
Section: Resultsmentioning
confidence: 63%
“…The results of selected-area electron diffraction patterns (SADPs) and EDS confirmed the successful preparation of ZIF-8@GO, with evidence of a (114) crystal plane and an inner element of ZIF-8 (Figure 1d2−d3). 34 The phase composition of ZIF-8@GO, ZIF-8, and GO was investigated, and the collected XRD spectra are shown in Figure 2a. Original GO exhibited a broad diffraction peak at ∼11.3°, corresponding to its (002) lattice plane.…”
Section: Resultsmentioning
confidence: 99%
“…It was found earlier in SEM studies that the stacking nature of the mixed-phase nanocrystals exhibited increased surface nanoroughness, which may enhance the antibacterial performance. Furthermore, this unique stacking of 80 ± 30 nm ZIF nanocrystals creates a 3D base with 2D sheets on the surface, resulting in uncoordinated ligands similar to ZIF-L on the surface and the high ability of Zn 2+ leaching. , Overall, the antibacterial efficiency of the ZIF-based coatings prepared in this work can be concluded as ZIF-L > ZIF-8, with one of the ZIF-L/ZIF-8 mixed-phase coatings outperforming all ZIF-L coatings.…”
Section: Resultsmentioning
confidence: 73%
“…Recently, a two-dimensional (2D), leaf-like ZIF was prepared using zinc salt and 2-methylimidazolate (Hmim) in aqueous solutions to form Zn­(mim) 2 ·(Hmim) 1/2 ·(H 2 O) 3/2 . , , Due to its porous nature and 2D structure, ZIF-L has been widely applied in numerous applications. More specifically, the ordered alignment of ZIF-L on membrane surfaces allows for regular aperture formations, which provide ideal water channels for rapid transportation of water molecules . Such properties have been further improved in recent studies owing to the alteration of the metal ion nodes .…”
Section: Introductionmentioning
confidence: 99%
“…When the 0.1 M 2mIm organic precursor was added, the structural change and internal etching of ZIF-L were significantly suppressed, thereby maintaining the ZIF-L structure ( Figure 3 b,e). Deacon et al reported a similar inhibition of the ZIF-L to ZIF-8 transformation [ 24 ]. It can be inferred that the high 2mIm concentration gradient in the solution phase could prevent the de-coordination of monodentate 2mIm from the ZIF-L surface.…”
Section: Resultsmentioning
confidence: 94%